Charter of the City of Newark and Laws of New Jersey Relating to Said City: Ordinances of the Common Council of the City of Newark 29 (1850) - (:unkn) unknown (My University, 1836)
An Ordinance Supplementary to a Law entitled "A Law for the appointment of a Street Commissioner and prescribing his duties," and for other purposes, 41 Discharging guns, &c.: No person shall, within the Lamp and Watch District, fire or discharge any gun, pistol, cannon, or fowling piece, or other fire arms, (unless in defence of his person or property,) nor let off any squibs, crackers, or other fireworks, in the city of Newark, unless by permission of the city authorities, under the penalty of five dollars for every offence."
Keywords: DISCHARGE